Lord and Minister Like Fish and Water: Xu Wei's Poems on Emperors Past and Present. (2nd January 2017) - Isaac Luper, Edward
Abstract : The artist and poet Xu Wei (1521–93) is well known for his eccentric and bohemian behavior as well as his powerful artistic expressiveness. With this in mind, mainland Chinese scholars have interpreted his work and poetry as representing indignation "against the entire feudal regime, " whilst Western scholars have held him up as an example or symbol of late Ming "individualism" and its implications of non-conformity, iconoclasm, and heterodoxy. However, by examining his poetry specifically on emperors and the relationships between emperor and subject, we can see a very different and more nuanced Xu Wei. Far from being "anti-feudal" or iconoclastic, Xu wrote of how he admired the martial prowess of the Wanli Emperor reviewing the troops and applauded strong and powerful emperors of the past such as the Hongwu Emperor, founder of the Ming dynasty. This not only challenges our conceptions of late Ming "individualism, " but also our conceptions of sixteenth-century literati views of the Ming emperor and his martial spectacles.